2018
DOI: 10.3389/fmicb.2018.01979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure, Reconstituted RTE Meat Microbiota, and Antimicrobials on Survival and Post-pressure Growth of Listeria monocytogenes on Ham

Abstract: Pressure treatment of ready-to-eat (RTE) meats extends the shelf life and reduces risks associated with Listeria monocytogenes. However, pressure reduces numbers of Listeria on ham by less than 5 log (CFU/g) and pressure effects on other meat microbiota are poorly documented. This study investigated the impact of pressure and RTE meat microbiota, with or without nisin and rosemary oil, on survival of Listeria after refrigerated storage. Ham was inoculated with a 5-strain cocktail of L. monocytogenes alone or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Indeed, a recent work carried out with a simplified ham microbiota (five species including Listeria monocytogenes, L. sakei, B. thermosphacta, C. maltaromaticum and Leuconostoc gelidum) showed that HPP treatment is not sufficient to inhibit growth recovery of the microbiota over long storage time (Teixeira et al, 2018). This is pointing out that there is a clear gap in our knowledge on the HPP efficiency towards various microbial communities which may be present on cooked ham.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent work carried out with a simplified ham microbiota (five species including Listeria monocytogenes, L. sakei, B. thermosphacta, C. maltaromaticum and Leuconostoc gelidum) showed that HPP treatment is not sufficient to inhibit growth recovery of the microbiota over long storage time (Teixeira et al, 2018). This is pointing out that there is a clear gap in our knowledge on the HPP efficiency towards various microbial communities which may be present on cooked ham.…”
Section: Discussionmentioning
confidence: 99%
“…HPP combined to biopreservation has also been studied (Oliveira et al, 2015). HPP treatment of cooked ham treated with bacteriocins has been shown to reduce the population of several bacterial pathogens or to prolong cold storage (Jofré et al, 2008a(Jofré et al, , 2008bLiu et al, 2012;Marcos et al, 2008;Teixeira et al, 2018). In the present study, we investigated the combined effect of HPP and biopreservation on the dynamics of bacterial communities of cooked ham with reduced level of nitrite salts.…”
Section: Introductionmentioning
confidence: 99%
“…Carvacrol was also previously reported to suppress inactivation of E. coli after pressure treatment in buffer, and reduced inactivation of B. cereus spores at a temperature of ≤65°C (Feyaerts et al., 2015; Luu‐Thi et al., 2015). However, the essential oils thymol and rosemary extract did not influence pressure inactivation L. monocytogenes and E. coli (Li & Gänzle, 2016; Teixeira, Repkova, Gänzle, & McMullen, 2018).…”
Section: High Pressure Combined With Antimicrobial Hurdlesmentioning
confidence: 99%
“…High pressure alone reduces cell counts of Listeria on ham by less than 5 log CFU/g, however, with competitive meat microbiota, treatment of 500 MPa, 5 °C for 3 min reduced the cell counts of Listeria by more than 5 log CFU/g (Hereu, Bover‐Cid, et al., 2012; Jofré, Garriga, & Aymerich, 2008; Teixeira et al., 2018). The role of a reconstituted competitive meat microbiota consisting of B. thermosphacta , C. maltaromaticum , Leuconostoc gelidum , and L. sakei on postpressure growth and survival of L. monocytogenes was explored on RTE ham after pressure treatment, showing that RTE meat microbiota prevented growth of Listeria with decisive influence on pressure treated ham during refrigerated storage (Teixeira et al., 2018). Competitive meat microbiota consisting of lactic acid bacteria inhibited growth of L. monocytogenes in meat products, which was attributed to the production of bacteriocins and organic acid (Bredholt, Nesbakken, & Holck, 1999; Schillinger, Kaya, & Lücke, 1991).…”
Section: High Pressure Combined With Antimicrobial Hurdlesmentioning
confidence: 99%
“…While studies have assessed the prevalence and survival of L. monocytogenes in RTE products including meats [13][14][15][16], seafood [15][16][17][18], dairy products [19][20][21], and vegetables [22][23][24], less information is known about how this pathogen persists in RTE refrigerated dips. For example, two studies have determined that L. monocytogenes is capable of growth in hummus when stored at refrigeration (4˚C) [25,26].…”
Section: Introductionmentioning
confidence: 99%